Persebaran Geografis dan Variasi Kearifan Lokal: Implikasi bagi Pelestarian Budaya - lasaiba, Mohammad Amin (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2023)
This study examines the geographical distribution and variation of local wisdom in Indonesia and its implications for cultural preservation. Local wisdom is traditional knowledge developed from the long-term interaction between communities and their environment, influenced by geographical conditions such as climate, topography, and natural resources. These geographical variations result in diverse forms of local wisdom that adapt to the physical and social environment. This study employs a literature review method by analyzing relevant literature to identify critical patterns and themes related to the relationship between geography and local wisdom. The findings indicate that geographical environments greatly influence local wisdom and are crucial in maintaining ecosystem balance and cultural identity. However, modern challenges such as globalization, urbanization, and environmental changes threaten the preservation of local wisdom. Therefore, preservation strategies involving systematic documentation, education, and cultural protection policies are needed. This study emphasizes the importance of preserving local wisdom to safeguard cultural heritage and environmental sustainability in Indonesia